Association of vitamin D deficiency with COVID‐19 infection severity: Systematic review and meta‐analysis. (12th July 2021) - Wang, Zhen; Joshi, Avni; Leopold, Kaitlin; Jackson, Sarah; Christensen, Stephanie; Nayfeh, Tarek; Mohammed, Khaled; Creo, Ana; Tebben, Peter; Kumar, Seema
Abstract: Background: We sought to evaluate the association between vitamin D deficiency and the severity of coronavirus disease 2019 (COVID‐19) infection. Methods: Multiple databases from 1 January 2019 to 3 December 2020 were searched for observational studies evaluating the association between vitamin D deficiency and severity of COVID‐19 infection. Independent reviewers selected studies and extracted data for the review. The main outcomes of interest were mortality, hospital admission, length of hospital stay and intensive care unit admission. Results: Seventeen observational studies with 2756 patients were included in the analyses. Vitamin D deficiency was associated with significantly higher mortality (odds ratio [OR]: 2.47, 95% confidence interval [CI]: 1.50–4.05; 12 studies; hazard ratio [HR]: 4.11, 95% CI: 2.40–7.04; 3 studies), higher rates of hospital admissions (OR: 2.18, 95% CI: 1.48–3.21; 3 studies) and longer hospital stays (0.52 days; 95% CI: 0.25–0.80; 2 studies) as compared to nonvitamin D deficient status. Subgroup analyses based on different cut‐offs for defining vitamin D deficiency, study geographic locations and latitude also showed similar trends. Conclusions: Vitamin D deficiency is associated with greater severity of COVID‐19 infection. Further studies are warranted to determine if vitamin D supplementation can decrease the severity of COVID‐19.